Applicant reaction to technology-mediated employment interview: a hybrid thematic analysis - Alias, Alizi; Mohd. Taib, Maisarah
The use of technologies has recently received much attention in personnel selection process. This includes the use of technology-mediated employment interviews in selecting potential individuals to be hired. Past literature has not only focused on the utility issue of the use of technology-mediated interviews, but research has been extended to the issue of applicant reactions to technology-mediated employment interviews. Past literature, however, has focused largely on quantitative analysis into applicant reactions to technology-mediated interview. The purpose of this study was to investigate qualitatively applicant reactions to technology-mediated interview. Data obtained from 46 job applicants applying for a job as research assistant were analysed using hybrid thematic analysis. Hybrid thematic analysis enabled identification of overarching themes that captured the phenomenon of applicant reaction as described by the job applicants. The analysis generated eight main categories: predictive validity perceptions, perceived job-relatedness, perceived process fairness, perceptions of organisational attractiveness, perceptions of organisation technological sophistication/effectiveness, intentions toward the organisation, perceived effective two-way communication and self-perception outcomes. The findings indicated that applicants reacted to mediums of interviewing even before they enter selection process and to some degree the reactions were carried over to during and after interview process.